An innovative approach to remodelling bioscience undergraduate final year projects to develop key transferable skills sought by graduate employers - Rana, Karan Singh; Bashir, Amreen; Pallett, Ross (Frontiers in Education, 2024)
Undergraduate Biomedical Science dissertations are the culmination of a student's academic journey and allow students to refine technical proficiencies, experimental design and data analysis. However, traditional dissertation projects may not fully meet the requirements of diverse student populations and employer's needs. This research project aims to assess the effectiveness of modifying the assessment format for finalyear projects, incorporating elements such as lay summaries, project proposals, scientific research papers, and oral poster defences. The objective was to cultivate higher-order critical thinking skills and enhance written and verbal communication competencies, in addition to developing a suite of transferable skills which are highly sought by employers. Quantitative data were primarily generated via end-of-module feedback reports and the module satisfaction survey. Students rated their confidence in a suite of transferable skills pre and post-completion of the project module using a four-point Likert scale. Staff perceptions (n = 30) and module board reports were also evaluated. For all data, a paired t-test for related groups was conducted. Thematic analysis was used to analyse qualitative data using the Braun and Clark Framework. The end-of-module feedback was overwhelmingly positive with all students agreeing that they were satisfied with the module. Students reported a statistically significant increase in confidence within eleven transferable skills which are considered core within the industry, for example, critical thinking, problem-solving and time management. Furthermore, the mean module mark increased following the module redesign from 66.3 ± 0.2% in 2019 to 70.9 ± 0.6% in 2020 (p =<0.05). Staff provided free text comments, reporting an overall improvement in the module, a reduction in workload and a better teaching experience. Students exhibited appreciation of the new module structure, assessment suit and creative liberty within the projects. The redesigned project module enhanced the teaching experience for staff, whilst students appreciated the diverse range of projects and assessments that featured shorter word limits and a creative flair. Universities must reinvent undergraduate dissertations to equip students with essential employability skills.